Aeolian sand accumulation and land desertification over the past 1, 500 years as revealed by two aeolian dunes in the Beiluhe Basin on interior Qinghai-Tibet Plateau, SW China. (10th March 2022) - Wang, Luyang; Wu, Qingbai; Fu, Ziteng; Jiang, Guanli; Liu, Yali; Xu, Kunming
Abstract: As an important region of desertification in China, the Qinghai-Tibetan Plateau (QTP) has attracted great attention. However, the study of land desertification history at the millennia-scale on the interior plateau is grossly inadequate. In a severely and rapidly desertifying area in the Beiluhe Basin on the interior QTP, grain-size distributions, sand particle morphologies, and 7 available optically stimulated luminescence (OSL) ages of sand sediment from two fixed aeolian dunes were obtained by several laboratory tests. Combining these results with plateau paleoclimate and contemporary aeolian sand activities in several adjacent regions, two phases of evident enhanced aeolian sand accumulation corresponding to desert expansion over the past 1500 years in the study region were identified. The first enhanced phase (850–700 a B.P.) might have been closely related to suitable trapping of denser vegetation cover and degradation of permafrost on the QTP as a consequence of warm and wet climates. Reactivation of local older sediments caused by cold and dry climates might have been responsible for the second enhanced phase (1400–1200 a B.P.). Permafrost plays an important role in aeolian sand accumulation and desertification on the QTP. However, expansion (or degradation) of permafrost has not always prevented (or promoted) aeolian desertification development on the QTP since the Last Glaciation Maximum (LGM, 21–14–12 ka B.P.). The effects of permafrost on aeolian desertification are governed by numerous factors such as preceding and current climate conditions, locations of permafrost and aeolian sand activity, and trap conditions due to vegetation and topography.